PEMBELAJARAN BAHASA INDONESIA MENUJU MASYARAKAT 5.0 - Hidayati, Eka Suci; Andani, Puput (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— Society 5.0 (Sosiety 5.0) is a concept that arises when many people are warmly discussing the discourse of Industry 4.0 with all its implications in various fields, including education. The Community Concept 5.0 first appeared in Japan in 2016 and has since spread and its basic concepts continue to be shaped. Society 5.0 is based on a variety of pillars, including Industry 4.0 and cybernetics or cybernics. Community Vision 5.0 demands transformation in learning. This paper will explain several aspects of Indonesian language learning in the perspective of